Attitudinal Meaning in COVID-19 Local Language Guidelines of Indonesia: A Systemic Functional Linguistic Study - Dini Sri Istiningdias; Lia Maulia Indrayani; Eva Tuckyta Sari Sujatna; Wagiati Wagiati (Badan Pengembangan dan Pembinaan Bahasa, 2021)
The Ministry of Education and Culture has published 3M's health protocol behavior change guidelines regarding the campaign to prevent COVID-19 transmission in 77 local languages of Indonesia. However, this research only focused on guidelines that used Sundanese as a local language in West Java. This research aimed to identify the types of attitudes and analyze the meanings that appear in these guidelines. The author used the theory of Martin and White (2005), namely the attitude subsystem as part of the appraisal system with Systemic Functional Linguistic approach which showed the author's evaluative attitude towards various things written to lead the readers. The result of this research showed that some information contained judgement both positive and negative side such as the authors found 15 clauses included in the affective indicator of the attitude subsystem in security meaning and four clauses satisfaction meaning. In addition, the authors found 16 clauses included in the attitude subsystem of judgment indicator referring to social esteem and three clauses referring to social sanction. The author also found 12 clauses included in the attitude subsystem of appreciation indicator referring to composition, five clauses referring to valuation, and two clauses referring to reaction. Based on the results of the analysis of each clause listed in the 3M health protocol behavioral change guidelines then the authors conclude that the message conveyed is positive attitude for the society. AbstrakKementerian Pendidikan dan Kebudayaan telah menerbitkan pedoman perubahan perilaku protokol kesehatan 3M terkait kampanye pencegahan penularan COVID-19 dalam 77 bahasa daerah di Indonesia. Namun, penelitian ini hanya berfokus pada pedoman yang menggunakan Bahasa Sunda sebagai bahasa daerah di Jawa Barat. Penelitian ini bertujuan untuk mengidentifikasi jenis-jenis sikap dan menganalisis makna yang muncul dalam pedoman tersebut. Penulis menggunakan teori Martin and White (2005) yaitu subsistem sikap sebagai bagian dari sistem penilaian dengan pendekatan Linguistik Sistemik Fungsional yang menunjukkan sikap evaluatif penulis terhadap berbagai hal yang ditulis untuk mengarahkan pembaca. Hasil penelitian menunjukkan bahwa beberapa informasi mengandung penilaian baik sisi positif maupun negatif seperti, penulis menemukan 15 klausa yang termasuk dalam indikator afektif subsistem sikap bermakna keamanan dan 4 klausa bermakna kepuasan. Selain itu, penulis menemukan 16 klausa yang termasuk dalam subsistem sikap indikator penilaian yang mengacu pada penghargaan sosial dan 3 klausa yang mengacu pada sanksi sosial. Penulis juga menemukan 12 klausa yang termasuk dalam subsistem sikap indikator apresiasi mengacu pada komposisi, 5 klausa mengacu pada penilaian, dan 2 klausa mengacu pada reaksi. Berdasarkan hasil analisis dari setiap klausa yang tercantum dalam pedoman perubahan perilaku protokol kesehatan 3M maka penulis menyimpulkan bahwa pesan yang disampaikan bermakna sikap positif bagi masyarakat.